Perencanaan Pembangkit Listrik Tenaga Surya (PLTS) dan Kelayakan Ekonomi Pada PT. Jasa Prima Logistik Kendari - Sapri D.; Caroline, Andi; Arnovan Bernad Patabang; Suryanto; Bhuana, Chandra (Politeknik Negeri Ujung Pandang, 2025)
Abstract: This study aims to design an Hybrid Solar Power Plant (PLTS) system specifically designed to meet the daily load requirements at the PT. JPLB SULTRA Building, as well as to reduce the Company's operational costs in energy costs. The research method used is descriptive analysis with numerical calculations based on theoretical foundations and simulations using HOMER Pro and PVSyst software. The planning process begins with a survey and data collection in the field to identify the electricity demand of the building, with a total energy demand estimated at around 30,527 kWh per day The results showed that a 7 kWp PLTS system was designed with 12 units of 580 Wp solar panels and one 10,200 W inverter connected in a hybrid system with PLN Grid. The annual energy production from PLTS is 11,339 kWh based on numerical calculations, while HOMER simulation produces 11,176 kWh per year, and PVSyst produces 10,712 kWh per year. From an economic feasibility perspective, the Net Present Value (NPV) is positive at Rp. 118,913,888, the Internal Rate of Return (IRR) is 13,89% > 7% (discount factor), and the Profitabilty Index (PI) is 1.98 > 1, indicating that this project is feasible to implement.